Dampak Jumlah Uang Beredar, Nilai Tukar Rupiah dan Suku Bunga Bi Rate Terhadap Inflasi di Indonesia setelah Krisis Global 2008 - Herlina, Deswita; Wirdianingsih, Windhi (Ecosains: Jurnal Ilmiah Ekonomi dan Pembangunan, 2023)
This study aims to determine how the response and how much the contribution of the Money Supply, Rupiah Exchange Rates and BI Rate on Inflation in Indonesia After the 2008 Global Crisis. The data used in this study are time series data in 2008.1 to 2018.12. This research uses quantitative methods and analyzed using Eviews 8, using the Vector Autoregression (VAR) method. The results of this study indicate that there is no cointegration on the Amount of Money Supply, Rupiah Exchange Rates and BI Rate on Inflation in Indonesia after the 2008 Global Crisis. In the granger causality test results, if we use the null hypothesis with a significant level of ten percent, we get a granger causality relationship namely: Exchange rates against inflation and Exchange rates against JUB. But if we use the null hypothesis with a significant level of five percent, a granger causality relationship is obtained, namely inflation against the BI rate and the BI rate against the exchange rate. Analysis using the Impluse Response Function shows that JUB tends to give a negative response to inflation. Whereas the exchange rate and the BI rate tend to provide a positive response to inflation. Analysis using Variance Decomposition shows that the BI rate has the largest contribution in the formation of inflation that is far greater than the JUB and Exchange Rates. The relationship between the BI rate and inflation shows the importance of monetary policy to control the rate of inflation in Indonesia.